Combination of Fibrinogen and High-sensitivity C-reactive Protein Measurements is Potential in Identification of Acute Coronary Syndrome - Djanggan Sargowo; Ferry Sandra (The Prodia Education and Research Institute (PERI), 2015)
BACKGROUND: Acute myocardial infarction (AMI) is one of cardiovascular diseases with high morbidity and mortality rates. Novel biomarkers that can detect accurately acute coronary syndrome (ACS) at early stage, are necessary to improve current strategies and/or to identify subjects who are at risk. Fibrinogen and high-sensitivity C-reactive protein (hs-CRP) roles in inflammation process could be potential for ACS early detection. This study was conducted to evaluate measurements of fibrinogen and hs-CRP on ACS.METHODS: An analytic observational study with cross sectional approach was conducted on patients with Troponin I positive. After signing informed consent, anamnesis and complete blood count were conducted. Besides that, liver function, renal function, and blood glucose tests were conducted as well. Samples of selected subjects were quantified with enzyme-linked immunosorbent assay (ELISA) for Troponin I, fibrinogen and hs-CRP. Then statistical analyses were performed.RESULTS: There were 76 subjects in each ACS and non-ACS groups. ACS group showed significant higher levels of both fibrinogen and hs-CRP compared to Non-ACS group (p=0.000). Among evaluated risk factors, diabetes mellitus (DM) (p=0.003) and hypertension (p=0.000) were significantly higher in ACS group than in non-ACS group. Among evaluated clinical factors, blood glucose (p=0.001) and age (p=0.000) were significantly higher in ACS group than in non-ACS group. Combination of fibrinogen and hs-CRP measurements showed the highest sensitivity (75.00%), specificity (80.26%), accuracy (77.63%), positive predictive value (79.19%) and negative predictive value (76.25%).CONCLUSION: Since fibrinogen and hs-CRP were increased in ACS group and combination of fibrinogen and hs-CRP measurements showed the highest sensitivity, specificity, accuracy, positive predictive value and negative predictive value, we suggest that combination of fibrinogen and hs-CRP measurements could give added value to identify ACS.KEYWORDS: fibrinogen, hs-CRP, biomarker, ACS, acute coronary syndrome, atherosclerosis, inflammation